A comparative study on the performance of sinking and milling micro-EDM for nanofinishing of tungsten carbide. (23rd August 2010) - Jahan, M.P.; Wong, Y.S.; Rahman, M.
Micro-electrical discharge machining (micro-EDM) is a flexible machining technique offering the possibility to produce freeform microstructures and micromoulds using hard-but-conductive materials like tungsten carbide (WC). It is desirable to obtain fine surface finish directly using micro-EDM when micromoulds and dies are machined, so that subsequent polishing can be avoided. This paper presents a comparative study between the performance of die-sinking and milling micro-EDM for the semi-finish and finish machining of WC. The comparison was conducted with respect to achieved material removal rate (MRR), relative electrode wear ratio (EWR), surface topography, average surface roughness (Ra) and peak-to-valley roughness (Rmax). It has been found that, micro-EDM milling is capable of generating smooth, shiny and defect-free surfaces with lower Ra and Rmax at comparatively higher MRR and lower EWR in the finish micro-EDM of WC. Moreover, the MRR in milling micro-EDM can further be increased at semi-finishing regime with the sacrifice of surface finish and EWR by increasing the electrode scanning speed. Comparing all the performance parameters, milling micro-EDM has been found to be the better option for semi-finishing and finishing of WC than die-sinking.